Soil characteristics are associated with gradients of big sagebrush canopy structure after disturbance. Issue 6 (11th June 2019) - Barnard, David M.; Germino, Matthew J.; Arkle, Robert S.; Bradford, John B.; Duniway, Michael C.; Pilliod, David S.; Pyke, David A.; Shriver, Robert K.; Welty, Justin L.
Abstract: Reestablishing shrub canopy cover after disturbance in semi‐arid ecosystems, such as sagebrush steppe, is essential to provide wildlife habitat and restore ecosystem functioning. While several studies have explored the effects of landscape and climate factors on the success or failure of sagebrush seeding, the influence of soil properties on gradients of shrub canopy structure in successfully seeded areas remains largely unexplored. In this study, we evaluated associations between soil properties and gradients in sagebrush canopy structure in stands that had successfully reestablished after fire and subsequent seeding treatments. Using a dataset collected across the Great Basin, USA, of sagebrush stands that had burned and reestablished between 1986 and 2013, we tested soil depth and texture, soil surface classification, biological soil crusts plus mean historical precipitation, solar heatload, and fire history as modeling variables to explore gradients in sagebrush canopy structure growth in terms of cover, height, and density. Deeper soils were associated with greater sagebrush canopy structure development in terms of plant density and percent cover, coarser textured soils were associated with greater sagebrush cover and density, and more clayey soils were typically associated with greater height. Biological crust presence was also positively associated with enhanced sagebrush canopy growth, but adding more demographically or morphologically explicit descriptions of biocrust communities did not improve explanatory power. Increasing heatload had a negative effect on sagebrush canopy structure growth, and increased mean annual precipitation was only associated with greater sagebrush height. Given that conservation and restoration of the sagebrush steppe ecosystems has become a priority for land managers, the associations we identify between gradients in post‐fire sagebrush canopy structure growth and field‐identifiable soil characteristics may improve planning of land treatments for sagebrush restoration and the understanding of semi‐arid ecosystem functioning and post‐disturbance dynamics.